PENGARUH PENGGUNAAN ALAT PERAGA BERBASIS KONSEP GEOMETRI PADA MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE - Sulaiman, Sulaiman (JURNAL E-DUMATH, 2015)
AbstractÂ The research is experimental research. This study aims to determine the difference in average mathematics students learning outcomes between learning with and without the use of props Pythagoras on cooperative learning model Think Pair Share (TPS). The population was all the students in second grade of SMP Negeri 1 Sukoharjo in the academic year 2014-2015. The samples of the research were taken by using the cluster random sampling technique.Data analysis is using chi-square test andstatistical t-test. Based onthe results ofhypothesis test obtained that there is difference in the averageresult of learningmathematicsbetween experimental classandcontrol class and the averageresults oflearning mathematicsin experimental class is higherthan in control class. Thus,the averageresult of learningthatlearningto usepropsPythagorasoncooperative learning modelThink Pair Share (TPS)is higherthanlearningwithout the use ofpropsPythagoras.Â Keywords:Props, Phytagoras, Think Pair Share